Effect of ceramic waste powder content and sodium hydroxide molarity on the residual mechanical strength of alkali-activated mortars - Erol, Ferhat; Al-mashhadani, Mukhallad M.; Aygormez, Yurdakul; Nis, Anil (ELSEVIER SCIENCE SA, 2023)
In the study, the effects of various ceramic waste powder (CWP) additions (5, 10, and 15%) and sodium hydroxide (SH) molarity (8 M and 16 M) on the residual mechanical properties of different ambient-cured alkaliactivated mortar (AAM) samples were investigated under the elevated temperatures (300, 600, and 900 degrees C) and freeze-thaw (100 cycles) attacks. The fresh (flowability, initial and final setting time, water absorption, and void ratio) and hardened (compressive and flexural strength, ultrasonic pulse velocity, and weight loss) state performances were evaluated. Also, XRD and SEM analyses were carried out. The findings pointed out that flowability enhanced up to 15% of CWP replacements. The initial and final setting time was reduced with higher molarity, while improved with further CWP incorporations. The water absorption and void ratio decreased with higher CWP incorporations and SH molarity. Moreover, mechanical strengths increased with time, which were found to be more with a higher CWP replacement ratio and SH molarity. After elevated temperature, the average compressive strength losses were about 50% at 600 degrees C and 85% at 900 degrees C, while average flexural strength losses were about 70% at 600 degrees C and 85% at 900 degrees C. Meanwhile, similar residual compressive strengths were obtained at elevated temperatures, irrespective of the SH molarity and CWP incorporations. However, both CWP incorporation and high SH molarity slightly enhanced the residual flexural strengths. After freeze-thaw attacks, an average of 23% compressive strength loss and 29% flexural strength loss was obtained, and almost similar mechanical strength losses were observed with varying SH molarity and CWP replacement ratio.
Keywords: Alkali-activated mortar; Freeze-thaw; Compressive strength; Elevated temperatures; Flexural strength; Ultrasonic pulse velocity; Residual strength; HIGH-PERFORMANCE CONCRETE; GEOPOLYMER CONCRETE; FLY-ASH; STEEL FIBERS; NANO-SILICA; DURABILITY; SLAG; METAKAOLIN; BEHAVIOR; Materials Science